Discriminação simples com mudanças sucessivas na função dos estímulos: aprendizagem em bebês - SILVA, Flávia Teresa Neves (2011)
This study investigated the acquisition of repeated shifts of simple discriminations (RSSD) in three infants. Animated images were presented on a touch sensitive screen. The procedure started off with a two-choice simple discrimination training (SD) with shifts in the stimulus function until all stimuli had functioned once as S+ and once as S-. Afterwards, all the three stimuli were presented in the same trial completing a RSSD cycle. Two of the infants learned the RSSD with the two–choice procedure and one infant learned the SD with two stimuli. The replacement of the stimulus sets throughout the training, characterized as a multiple exemplar training, seems to have contributed to the infants' engagement in the task as well as to the acquisition of the discriminations.